Anti-Bacterial Activity Test of Carrot Tuber Ethanol Extract Hydrogel Preparation (Daucus Carota L.) in Inhibiting the Growth of Bacteria and Their Ability in the Healing Process of Grade II Burns on Wistar Rat (Rattus Norvegicus) - Welly Ria Utami Lubis; Ali Napiah Nasution; Hanjaya; Alvin Abrar Harahap; Muhammad Nawal Hasya; Jeri Yuliansyah; Ermi Girsang (PT FORMOSA CENDEKIA GLOBAL, 2023)
Carrots are root vegetables that are very common in Indonesia. Carrot plant (Daucus carita L.) is a root vegetable plant that has a high content of beta carotene, rich in dietary fiber, natural antioxidants and high vitamin A which is 12,000 IU. The reddish-yellow color of carrots is due to the high content of carotene pigment. The sample used in this study was fresh carrot tubers. The tubers are separated from other impurities and then washed thoroughly and then drained and weighed. Next, the tubers are dried at a temperature of 30-40oC until the tubers are dry (marked when broken brittle). Simplisia that has dried (brittle) is powdered with a blender and stored in a tightly closed container and stored at room temperature. The preparation of the extract is carried out by maceration using 70% ethanol solvent. According to the Indonesian Herbal Pharmacopoeia (2008), as much as 1 part of simplisia dry powder is put into the maserator, added 10 parts of solvent. Soak for the first 6 hours while stirring occasionally, then let stand for 18 hours. Separate the maserat by filtering. Repeat the extraction process at least twice with the same type and amount of solvent. Furthermore, all the mafiber is collected, then evaporated with a rotary evaporator at a temperature of ±50oC until a thick extract is obtained. The results showed that ethanol extract of carrot tubers with a simplisia weight of 500 grams produced a yield of 3.78% with an extract weight of 68.9 grams. The results below show that carrot tuber ethanol extract shows phytochemical screening results that contain flavonoids, alkaloids, glycosides, tannins and steroids. The results of the measurement of the diameter of the inhibitory zone above showed that ethanol extract of carrot tubers (Daucus carota L.) can inhibit the growth of Pseudomonas aeruginosa and Staphylococcus aureus bacteria at concentrations of 10-400 mg / mL. The measurement results obtained the diameter of the inhibitory zone with a strong inhibitory zone response category at all concentration variations. It was found that high concentrations had activity that did not differ significantly from low concentrations. Carrot tuber ethanol extract has a significant difference (p < 0.05) when compared to the positive and negative groups while the results of the measurement of bacterial killing power above show that carrot tuber ethanol extract (Daucus carota L.) can inhibit the growth of Pseudomonas aeruginosa and Staphylococcus aureus bacteria at concentrations of 10 – 100 mg / mLl